Physiology and Pathophysiology of the Swallowing Area of Human Motor Cortex - S. Hamdy; Q. Aziz; D. G. Thompson; J. C. Rothwell (Neural Plasticity)
Swallowing problems can affect as many as one in three patients in the period immediately after stroke. Despite this, in the majority of cases, recovery usually occurs to a safe level after a month or two. In this review, we show. how the organization of the cortical projections to swallowing nuscles can account for many of the clinical observations on swallowing after stroke and explain why recovery is common in the long term. In addition, we examine approaches that may be useful in speeding up recovery of swallowing. Swallowing may be a useful model in which to study central nervous reorganization after injury.